PENGARUH HEALTH EDUCATION DENGAN METODE LEAFLET TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DI RSUD Prof. Dr. SOEKANDAR KABUPATEN MOJOKERTO - Virda Yuniarti, Enny; Agus Parka M.Y, Putu (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Effective surgical operation or emergency is tightening complex event, so not only have physic disturbed but also have psychologist disturbed. Surgical procedure will always be preceded emotional reaction by patient, which is anxiety. Anxiety that happened by patient need attention and inherency nursing care, because emotional condition of patient will influent body function toward operation. Client anxiety level that related with pre-operation action can be decreased with giving health education (HE). The purpose of this research is to analyze influence HE with leaflet method about anxiety level of pre-operation patient in RSUD Prof. Dr. Soekandar Kabupaten Mojokerto, research design that used in this research is pre-experiment design (one group pre test – post test) with probability sampling technique that is total sampling, with samples total 16 person at 24 May – 07 June 2014. The data analysis used Wilcoxon Signed Rank Test with significant standard 95% (α = 0,05), obtain p value is 0,000 it’s means that there is influence health education with leaflet method about anxiety level of pre-operation patient in RSUD Prof. Dr. Soekandar Kabupaten Mojokerto. Leaflet is information media or healthy message about special problem, through a piece of paper that be folded to small size. The use of leaflet in information will help imagination of client, comprehension about information that receive and leaflet as simply tool reminder message which the reader can study itself, information that get. So that can help push down and can decrease anxiety of client.Key Words: health education, leaflet, anxiety, pre-operation